Os efeitos da música clássica sobre sintomas comportamentais da demência em pessoas idosas institucionalizadas: estudo quase-experimental - Siqueira, Bianca Franceschini (2023)
Introduction: Dementia is a condition that affects the cognitive ability of elderly people and can significantly impact their behavior. Musical intervention has been considered a promising alternative for the treatment of cognitive and behavioral disorders in elderly people with dementia. Method: Descriptive-exploratory, quasiexperimental study, with 14 institutionalized older people. Eight sessions of music listening took place over two months. A Sociodemographic Questionnaire, Neuropsychiatric Inventory, Facial Action Coding System and Body Movement Assessment were used. Results: The majority were women, with an average institutionalization time of 16.6 months, an average use of 2.6 medications per day, and the prevalent dementia was Alzheimer's disease. There was a statistically significant decrease (p<0.005) in the severity of depression and motor disturbance symptoms, as well as a decrease in caregiver burden regarding depression and apathy symptoms. During the music sessions, the most observed emotion was joy, and the least observed was fear. All participants presented movements in the headtrunk area.Conclusion: The musical intervention was effective in reducing the severity of some symptoms in elderly people with dementia and also reduced caregiver burden related to these symptoms, in addition to stimulating positive movements and emotions.